Modelos de ordem frácionaria empregado no estudo da cinética de secagem de soja - Matias, Gustavo de Souza (2018)
Drying is a decisive step in the quality of the grains, since it is through it that the chemical physical stabilization of the grains of fashion is guaranteed to guarantee their preservation during storage. Drying also allows the anticipation of the harvest in order to avoid losses due to climatic inclement weather. If the drying process is not well controlled, harmful damage to the material can occur, so effective control of the process is required. In the control of drying processes in general, whole-order models are employed, since there are still few applications of models of fractional order in drying. In this work we propose the application of fractional order models in the adjustment of the kinetics of soybean drying. Initially the Friesen generalized order kinetic equation was adjusted, in the sequence a new generalized order semi-empirical equation is proposed. By adjusting both equations of generalized order to the kinetic data of soybean drying, we obtained models of fractional order. These models of fractional order were compared with classic models of drying in order to present good adjustments, having similar or superior results to the classic models of drying